EFFECT OF BIOFUMIGATION ON POTATO CYST NEMATODES - Bairwa, Aarti (Potato Journal, 2016)
Potato cyst nematodes (PCN) Globodera rostochiensis (Woll) and G. pallida (Stone) are quarantine organisms that hinder the sustainable production of potato in the Nilgiris hills of Tamil Nadu. It remains as a serious endemic pest of potato in this region due to intensive cultivation of potato and favourable climatic conditions. Hence field experiments were conducted to evaluate the efficacy of bio-fumigation by incorporating chopped residues of radish, cabbage and cauliflower in potato cv. Kufri Giriraj. One set of treatments were covered with transparent polyethylene sheets for 4 weeks before planting and another set was left uncovered. The biofumigants were compared with the chemical nematicide carbofuran @ 2 kg a.i /ha. The treatments were replicated thrice in a randomized block design. The results revealed that all the treatments significantly increased the potato yield and decreased the nematode population. Incorporation of radish leaves at 1 kg/m2 and covering with polyethylene sheet recorded maximum growth parameters, yield (25.97 t/ha) and minimum PCN reproduction factor (Rf) 1.21. It was on par with carbofuran treatment which yielded 25.09 t/ha and PCN reproduction factor (Rf) 1.24 and was followed by cabbage and cauliflower residues covered with polyethylene sheet.